Horticultural Reviews 2000
DOI: 10.1002/9780470650806.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Tomato Fruit Quality

Abstract: To investigate the effects of low temperature (LT) and weak light (WL) on tomato (Solanum lycopersicum L., cv.) during flowering and fruit-setting periods, a controlled experiment was conducted. Two levels of day/night temperature and PAR were set: S1 (18/8°C, 200 µmol m -2 s -1 ), S2 (12/2°C, 200 µmol m -2 s -1 ), S3 (18/8°C, 80 µmol m -2 s -1 ), and S4 (12/2°C, 80 µmol m -2 s -1 ), taking 28/18°C and 600 µmol m -2 s -1 as control (CK). The results showed that during stress stage, the Chlorophyll (Chl) a, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(186 citation statements)
references
References 253 publications
10
160
0
11
Order By: Relevance
“…Food loss levels can be derived from both qualitative and quantitative auditing at each stage in the wholesale marketing of fruits and vegetables. These types of losses within a food supply chain can be difficult to determine [16,38]. Generally, losses associated with quality are usually identified by a decrease in the market value of the produce [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food loss levels can be derived from both qualitative and quantitative auditing at each stage in the wholesale marketing of fruits and vegetables. These types of losses within a food supply chain can be difficult to determine [16,38]. Generally, losses associated with quality are usually identified by a decrease in the market value of the produce [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants were not requested to provide information regarding any qualitative fruit and vegetable losses, but were asked their reasons for not selling and their opinions on future loss reduction and utilization methods. The reason behind this approach stems from previous studies that showed qualitative losses were much more difficult to determine than quantitative losses [16,38]. Importantly, poor produce quality attracts little consumer interest since factors such as appearance, taste, texture, and nutritional value are expected for premium quality fruits and vegetables [39].…”
Section: Survey Methods and Questionnairesmentioning
confidence: 99%
“…The concentration of sugars may vary from 1.66 to 3.99% and 3.05 to 4.65% of the fresh matter, as a function of the cultivar and cultivation conditions, respectively [63]. As with the sugars, the organic acids are crucial to the flavour of the fruits.…”
Section: Index Of Maturity and Taste Indexmentioning
confidence: 99%
“…Para la variable firmeza de la fruta (Figura 1), el gráfico presenta una tendencia creciente lineal con el aumento de frecuencias de riego. La firmeza y la cantidad de agua son los principales atributos que determinan la calidad del almacenamiento de los frutos de tomate (Batu, 2004.;Dorais et al, 2001. ; Viskelis et al, 2008).…”
Section: -Resultados Y Discusiónunclassified